Transcriptome Responses to Defined Insecticide Selection Pressures in the German Cockroach (Blattella germanica L.) - Scharf, Michael E.; Wolfe, Zachery M.; Raje, Kapil R.; Fardisi, Mahsa; Thimmapuram, Jyothi; Bhide, Ketaki; Gondhalekar, Ameya D. (Frontiers in Physiology, 2022)
Cockroaches are important global urban pests from aesthetic and health perspectives. Insecticides represent the most cost-effective way to control cockroaches and limit their impacts on human health. However, cockroaches readily develop insecticide resistance, which can quickly limit efficacy of even the newest and most effective insecticide products. The goal of this research was to understand whole-body physiological responses in German cockroaches, at the metatranscriptome level, to defined insecticide selection pressures. We used the insecticide indoxacarb as the selecting insecticide, which is an important bait active ingredient for cockroach control. Six generations of selection with indoxacarb bait produced a strain with substantial (>20x) resistance relative to inbred control lines originating from the same parental stock. Metatranscriptome sequencing revealed 1123 significantly differentially expressed genes in > two of three statistical models (81 upregulated and 1042 downregulated; FDR p<0.001; log2FC of +/- 1). Upregulated DE genes represented many detoxification enzyme families including cytochrome-P450 oxidative enzymes, hydrolases and glutathione-S-transferases. Interestingly, the majority of downregulated DE genes were from microbial and viral origins, indicating that selection for resistance is also associated with elimination of commensal, pathogenic and/or parasitic microbes. These microbial impacts could result from: (i) direct effects of indoxacarb, (ii) indirect effects of antimicrobial preservatives included in the selecting bait matrix, or (iii) selection for general stress response mechanisms that confer both xenobiotic resistance and immunity. These results provide novel physiological insights into insecticide resistance evolution and mechanisms, as well as novel insights into parallel fitness benefits associated with selection for insecticide resistance.